Projecto FCT PTDC/CPO-CPO/28748/2017 - Relatório de Progresso 2019 - Marchi, R. (2019)
Brief Description: Media and Intelligence have detected a growing Internet activism of the Portuguese Radical Right (PRR), associated with the emergence of two New Euro-American Radical Right (NEAR) streams: the North-American Alt-Right and the European Identitarianism. Both of them have a strong capacity to generate popular youth culture (creative terminology, media-activism, online militancy). The research project analyses the growth of this PRR propelled by the circulation, reception and reproduction of NEAR ideas and practices. The aims of the project are the following: 1) to explain the reproduction of NEAR ideas and practices in Portugal, both online and offline; 2) to map the Portuguese participation in the NEAR international networks; 3) to understand how deeply the NEAR is shaping the on-going developments of the PRR. Methodologically, the in-depth Portuguese case study will be compared with other successful and unsuccessful foreign cases to assess if and how the NEAR can turn the PRR into a more relevant political player within the national right-wing milieu. Summary: The most recent reports of the Portuguese Information and Security Services (SSI) have detected an increase in radical right activism throughout the Internet. This phenomenon can be verified not only in Portugal but also in many European countries and it is associated with the emergence of two innovative right wing radical streams: the North-American Alt-Right and the French-Italian Identitarian movement. The relevance of these two streams is evident in the Alt-Right’s prominence amidst the election of Donald Trump – with Trump’s chief strategist Steve Bannon being a leading element of the Alt-Right – and in the Identitarian success within Marine Le Pen’s electoral base. The two streams have shown a strong capacity to generate popular culture among the youngest generations through memes, creative terminology, media-activism and online militancy. Starting from the concerns of the Institutions and Media, this research project aims to improve the knowledge of this growing right-wing radicalism in Portugal. Specifically, it aims at analysing the effects of the circulation, reception and reproduction of ideas and practices produced by the Alt-Right-Identitarian transatlantic interaction. The objective is to understand how this acceleration in the circulation of ideas and practices can lead to the development of a new radical right in Portugal in the same way it happened with other successful countries; that is, through the social movements of a young generation of militants with a high potential for setting the ideological directions of future right wing parties and mobilizations. This research project has three particular goals. The first one is to identify how deeply this Alt-Right-Identitarian interaction has entered the Portuguese right wing milieu (both radical and mainstream) and influenced its ideological traditional roots. The second one is to map the online participation of Portuguese militants in (inter)national networks, stimulated by the internet activism of the Alt-Right and the Identitarian milieu. The third one is to describe and explain the reproduction of political mobilization practices, both online and offline, promoted in Portugal by the more successful experiences coming from abroad. These goals will be reached through an in-depth Portuguese case study and its comparison with different countries in order to understand how successful or unsuccessful this Alt-Right-Identitarian influence is within their national radical right areas. The comparison between an already successful area (e.g. France, Italy, Austria) with an area in ongoing consolidation (e.g. Portugal and Spain) will permit to assess if and how this new Euro-American interaction can energize the creation of a Portuguese radical right operating as a more relevant political player. By gathering several experts, the research project intends to shed light on this important and yet academically undocumented phenomenon.